Language convergence: linguistic aspect of COVID-19 - Balabekova, М.А.; Vesselinov, D.; Khan, N.K. (KU Publ., 2021)
Events on a global scale always leave their mark on the language of society, and today, the coronavirus (COVID-19) is one of those. The article is devoted to the study of new language trends in Kazakhstan. The authors of the article consider the peculiarities of language development in a pandemic. The purpose of this work is to carry out a comprehensive linguistic study of the mechanisms of language convergence and to analyze the new words associated with the pandemic functioning in the mass media of Kazakhstan. The characteristic features of the media platform, which is used as a government tool to strengthen the morale of citizens raising the spirit of heroism and support during a pandemic, are analyzed. In addition to it, the authors revealed the importance of the military metaphor in articles related to the coronavirus pandemic. COVID–19 gave rise to a number of neologisms describing a new reality that people faced during a pandemic: коронаре- альность, корона-глобализация, коронашторм, коронаблокировка, коронакризис, коронашейминг, etc. Most common words and phrases turned out to be previously existed in the language, and undergone a semantic shift in 2020: маска, контактер, корона, зумер, etc.
Тіл конвергенциясы: COVID-19 кезеңінің тілдік аспектісі
Конвергенция языков: лингвистический аспект COVID–19
Keywords: COVID–19; coronovirus; neologisms; word-formation; covid; borrowings; language convergence